Diagnosis and Optimal Surgical Treatment Strategy Selection for Asymptomatic Large Cardiac Myxomas: Review of Modern Approaches and Own Clinical Case Presentation - Osaulenko, Vyacheslav V.; Hubka, Viktor O.; Chmul, Karina O.; Nakonechnyi, Serhii Yu.; Budagov, Rasim I. (Ukrainian Journal of Cardiovascular Surgery, 2024)
Cardiac myxoma (CM) is the most common primary tumor of the heart and can be asymptomatic for a long time. CMs have an increased risk of systemic embolization, intracardiac obstruction, transient ischemic attacks, and strokes, potentially leading to patient disability and/or sudden cardiac death. The aim. To highlight the data of modern scientific literature and demonstrate a case of plastic reconstruction of the heart after resection of a large tumor. Materials and methods. We report a case of incidentally discovered left atrial myxoma in a 67-year-old woman with no significant medical history. Transthoracic echocardiography revealed a large mass located in the left atrium. An open surgical intervention was performed, during which the giant CM was completely removed. Histopathological examination confirmed the diagnosis. The patient was discharged on the 7th day of the postoperative period without any complaints. Also, we carried out a comprehensive search and analysis of previously published cases of asymptomatic myxomas and methods of their surgical treatment in the scientific literature of the main electronic databases. Results. In our proposed report, a satisfactory clinical outcome was obtained in a patient with giant myxoma who underwent open cardiac surgery. According to the current literature, transthoracic echocardiography, computed tomography and magnetic resonance imaging of the heart are the gold standards for the diagnosis of heart neoplasms, which corresponded to our diagnostic algorithm. In the opinion of most specialists, the minimally invasive approach is a promising and attractive treatment method for surgeons, however, a complete median sternotomy remains the standard approach in patients with CMs. Conclusions. Asymptomatic CM is a rare incidental finding with a high probability of serious adverse cerebral and cardiovascular events. Early diagnosis of CM is crucial to prevent life-threatening complications, and the most valuable tool is transthoracic echocardiography. The strategy of surgical treatment varies depending on their size and anatomical localization, in particular, resection of large and septal myxomas is usually performed through median sternotomy.